2011
DOI: 10.1007/s12185-010-0763-x
|View full text |Cite
|
Sign up to set email alerts
|

Two case reports of inherited antithrombin deficiency: a novel frameshift mutation and a large deletion including all seven exons detected using two methods

Abstract: An inherited antithrombin deficiency is an autosomal dominant thrombotic disorder. We identified two pedigrees of inherited type I antithrombin deficiency and two responsible mutations in each. A novel 21-22delAA appeared to have caused a frameshift with a premature termination at amino acid +63 in one patient and a large deletion including all seven exons was identified by multiplex ligation-dependent probe amplification in the other. Some asymptomatic relatives of the second patient had the same mutation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Venous thromboembolism (VTE) for long has been perceived to be less common in Asian population compared to western population [ 12 ]. However, population-based epidemiological study in Asian countries has demonstrated an increasing incidence of VTE in Asians annually [ 12 ] and mutations of AT gene in Asian population has been reported [ 13 15 ]. Although the first report of AT deficiency in an Indian family dates back to 1982 [ 16 ], yet no mutation has been identified in Indian population till date.…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) for long has been perceived to be less common in Asian population compared to western population [ 12 ]. However, population-based epidemiological study in Asian countries has demonstrated an increasing incidence of VTE in Asians annually [ 12 ] and mutations of AT gene in Asian population has been reported [ 13 15 ]. Although the first report of AT deficiency in an Indian family dates back to 1982 [ 16 ], yet no mutation has been identified in Indian population till date.…”
Section: Introductionmentioning
confidence: 99%